Associations Between Service Members' Posttraumatic Stress Disorder Symptoms and Partner Accommodation Over Time. Issue 3 (28th December 2020) - Allen, Elizabeth; Renshaw, Keith; Fredman, Steffany J.; Le, Yunying; Rhoades, Galena; Markman, Howard; Litz, Brett
Abstract: When service members manifest symptoms of posttraumatic stress disorder (PTSD), intimate partners may engage in behaviors to accommodate their partners' experiences (e.g., helping service members avoid situations that could make them uncomfortable, not expressing own thoughts and feelings to minimize PTSD‐related conflict), which may inadvertently serve to maintain or increase PTSD symptoms over time. In a sample of 274 male service member/female civilian couples, we evaluated hypothesized bidirectional pathways between self‐reported service member PTSD symptoms and partner accommodation, assessed four times over an approximately 18‐month period. A random‐intercept cross‐lagged panel model disaggregating between and within effects revealed that, on average, couples in which the service member had higher levels of total PTSD symptoms also scored higher in partner accommodation, between‐couple correlation, r = .40. In addition, at time points when service members' PTSD symptoms were higher relative to their own average symptom level, their partners' level of accommodation was also higher than their personal average, within‐couple correlation r = .22. Longitudinally, service member PTSD symptom scores higher than their personal average predicted subsequent increases in partner accommodation, β = .19, but not vice versa, β = .03. Overall, the findings indicate both stable and time‐specific significant associations between service member PTSD symptoms and partner accommodation and suggest that higher levels of PTSD symptoms are a significant driver of later increases in partner accommodation. These findings add further support for treating PTSD in an interpersonal context to address the disorder and concomitant relational processes that can adversely impact individual and relational well‐being. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0168.R2_Allen_Cantonese Traditional Chinese 軍役人員的創傷後壓力症症與伴侶接納之間的關聯 摘要: 當軍人表現出創傷後壓力症(PTSD)的症狀時, 親密伴侶可能會採取一些行為來適應其伴侶的經歷(例如, 幫助軍人避免可能使他們感到不舒服的情況, 不表達自己的想法和感受以盡量減少與創傷後壓力症有關的衝突), 這可能無意中起到維持或增加創傷後壓力症症狀的作用。在274對男性軍人/女性平民夫婦的樣本中, 我們評估了自我報告的軍人創傷後壓力症症狀和伴侶接納之間的假設的雙向路徑, 在大約18個月的時間裡評估了4次。一個隨機截距交叉滯後的面板模型分解了之間和內部的影響, 平均而言, 服役人員創傷後壓力症總症狀水平較高的夫妻在伴侶接納、夫妻間相關性(r = 0.40)方面的得分也較高。此外, 在服役人員的創傷後壓力症症狀相對於他們自己的平均症狀水平較高的時間點, 他們的伴侶的適應水平也高於他們的個人平均水平, 夫妻內相關係數r = .22。從縱向看, 軍役人員創傷後壓力症症狀得分高於他們的個人平均水平, 預示著隨後伴侶的適應性增加, 即β = .19, 但反之則不然, β = .03。總體而言, 研究結果表明, 軍役人員創傷後壓力症症狀和伴侶接納之間有穩定的和特定時間的重要聯繫, 並表明創傷後壓力症症狀水平較高是後來伴侶接納增加的重要驅動因素。這些發現進一步支持在人際關係背景下治療創傷後壓力症, 以解決障礙和伴隨的關係過程, 這可能對個人和關係的幸福產生不利影響。 Simplified Chinese 军役人员的创伤后压力症症与伴侣接纳之间的关联 摘要: 当军人表现出创伤后压力症(PTSD)的症状时, 亲密伴侣可能会采取一些行为来适应其伴侣的经历(例如, 帮助军人避免可能使他们感到不舒服的情况, 不表达自己的想法和感受以尽量减少与创伤后压力症有关的冲突), 这可能无意中起到维持或增加创伤后压力症症状的作用。在274对男性军人/女性平民夫妇的样本中, 我们评估了自我报告的军人创伤后压力症症状和伴侣接纳之间的假设的双向路径, 在大约18个月的时间里评估了4次。一个随机截距交叉滞后的面板模型分解了之间和内部的影响, 平均而言, 服役人员创伤后压力症总症状水平较高的夫妻在伴侣接纳、夫妻间相关性(r = 0.40)方面的得分也较高。此外, 在服役人员的创伤后压力症症状相对于他们自己的平均症状水平较高的时间点, 他们的伴侣的适应水平也高于他们的个人平均水平, 夫妻内相关系数r = .22。从纵向看, 军役人员创伤后压力症症状得分高于他们的个人平均水平, 预示着随后伴侣的适应性增加, 即β = .19, 但反之则不然, β = .03。总体而言, 研究结果表明, 军役人员创伤后压力症症状和伴侣接纳之间有稳定的和特定时间的重要联系, 并表明创伤后压力症症状水平较高是后来伴侣接纳增加的重要驱动因素。这些发现进一步支持在人际关系背景下治疗创伤后压力症, 以解决障碍和伴随的关系过程, 这可能对个人和关系的幸福产生不利影响。